A follow up study of postpartum intrauterine device insertion in a tertiary health care centre - Ranjana, .; Verma, Anita; Chawla, Indu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In view of high rate of unintended pregnancy in our country, particularly in post-partum women, there is a need for reliable, effective and long-term contraception such as intrauterine device (IUCD) in post-partum women. This study was done to determine the efficacy and safety of Post-Partum Intrauterine Device (PPIUCD) and to compare the outcomes of PPIUCD insertion after vaginal delivery and caesarean section. Methods: This follow up study was carried out in the department of Obstetrics and Gynecology, Dr. R.M.L Hospital, PGIMER, New Delhi over a period of 7 month from January 2016 to July 2016. PPIUCD (cu T- 380 A) insertions were done in 136 women who fulfilled the inclusion criteria. Women having haemoglobin less than 8 gm%, rupture of membranes more than 18 hours, obstructed labour, Uterine anomalies, distorted uterine cavity by fibroid, significant postpartum haemorrhage, coagulation disorders, fever or clinical symptoms of infection during labour were excluded from the study. Post insertion counselling was done, and these women were advised to follow up at 6 weeks and then after 6 months postpartum in the family planning O.P.D. At the follow-up visit, the women were asked for any symptoms of unusual vaginal discharge, irregular or heavy bleeding per vagina, and any expulsions if noticed. Results: Total number of cases that reported for follow up in family planning OPD was 118. Therefore, 18 patients were lost in the follow up. In 58.47% women, there was no complaint. Heavy menstrual bleeding was found in 17.79% women and pelvic pain in 16.10% women. The expulsion rate was 5.08% and IUCD removal was done in 12.71% women. Though, the incidence of expulsion and removal rate was more in vaginal insertions than in caesarean insertions but this difference was not statistically significant, while the incidence of missing threads were found more in intra caesarean insertion (28% vs. 11.76% with p value <0.05). Continuation rate at 6 month was 82.20%. Conclusions: PPIUCD insertion is a safe, convenient and effective method of contraception. Although the expulsion rate and removal rate was more in vaginal PPIUCD insertions, the benefits of providing highly effective contraception immediately after delivery outweigh this disadvantage, particularly in our country where most of the women do not come for contraceptive advice after delivery.